2011
DOI: 10.1155/2011/483242
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Training Module Improves Recognition of Echocardiographic Wall-Motion Abnormalities by Emergency Medicine Physicians

Abstract: Objective. Wall-motion abnormality on echocardiogram is more sensitive in detecting cardiac ischemia than the electrocardiogram, but the use of bedside echocardiography by emergency physicians (EPs) for this purpose does not appear to be widespread, apparently due to limited data on proficiency of EPs for this task. We sought to determine the effect of a brief training module on the ability of EPs to recognize wall motion abnormalities on echocardiograms. Methods. We developed a brief training and testing modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“… 7 , 8 Proctored US hands-on instruction and training modules have been shown to positively impact US training; however, to our knowledge, US-focused simulation-based training has not been studied before. 9 , 10 This study evaluated a novel simulation-based US educational and assessment workshop.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Proctored US hands-on instruction and training modules have been shown to positively impact US training; however, to our knowledge, US-focused simulation-based training has not been studied before. 9 , 10 This study evaluated a novel simulation-based US educational and assessment workshop.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there exists only one paper evaluating the ability of non-cardiologist clinicians to diagnose wall-motion abnormalities. This study showed that a 30-minute training module significantly improved the ability of emergency physicians to identify wall motion abnormalities (53). Though this has not been studied directly, we postulate that a negative exam performed and interpreted by a non-cardiologist clinician, given the skill required in image acquisition and interpretation, does not rule out the presence of wall motion abnormalities.…”
Section: Wall Motion Abnormalities Q: Is There Any Obvious Wall Motiomentioning
confidence: 72%
“… 7 , 9 , 17 However, one prospective study did show that basic echocardiography training for emergency department physicians greatly improved their ability to interpret WMAs. 18 Two previous case series evaluating the use of point-of-care echocardiography by emergency department physicians concluded that echocardiography can provide a rapid detailed assessment of WMAs that may help speed clinical decision-making. 19 , 20 Detecting early WMAs may be imperative, as these occur even before electrocardiographic changes or chest pain in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%